2018
DOI: 10.1007/s13668-018-0255-9
|View full text |Cite
|
Sign up to set email alerts
|

Child, Caregiver, Family, and Social-Contextual Factors to Consider when Implementing Parent-Focused Child Feeding Interventions

Abstract: Purpose of Review: Interventions that aim to alter child eating behaviors often focus on parents as a proximal influence. Yet, parents can be difficult to engage. Therefore, intervention recommendations are often not implemented as designed. The goal of this review is to highlight factors at multiple contextual levels that are important to consider when developing interventions to address child eating, due to their implications for overcoming parent engagement challenges. Recent Findings: Intervention studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 68 publications
0
15
1
1
Order By: Relevance
“…It is likely that weight perception and concern were not major contributing factors of maternal feeding practices. Another possible explanation is that important factors related to maternal feeding practices might have been missed [50]. Compared to mothers recruited in other studies [17,25,31], mothers in our study showed a relatively low level of weight concern.…”
Section: Discussioncontrasting
confidence: 54%
“…It is likely that weight perception and concern were not major contributing factors of maternal feeding practices. Another possible explanation is that important factors related to maternal feeding practices might have been missed [50]. Compared to mothers recruited in other studies [17,25,31], mothers in our study showed a relatively low level of weight concern.…”
Section: Discussioncontrasting
confidence: 54%
“…Principles of motor learning should be kept in mind when treating both infants who are learning to swallow and in retraining swallowing with older children ( 109 ). Parent education and training are essential components of any feeding therapy provided to infants and young children ( 110 ). Patients with a history of congenital heart disease have increased incidence of baseline feeding and swallowing difficulties ( 111 , 112 ) and may require extensive feeding therapy, extending beyond the inpatient admission, to target acceptance of oral feeds and oral motor skills.…”
Section: Rehabilitation Programsmentioning
confidence: 99%
“…A large number of factors (e.g., child social/cultural, neighborhood) influence child dietary intake [39]. What are the most common categories of child perception of eating events?…”
Section: Child Response Predispositionmentioning
confidence: 99%
“…Greater variability on the responsiveness and demandingness scales may have led to differences in the selection of FPP, especially among parents at the extremes of the distributions. Some children will be in the care of different caregivers, e.g., mother, grandparent, daycare provider, likely some of whom will vary in their feeding style and parenting practices [39]. Conflicts will likely arise in FPP across caregivers.…”
Section: Selection and Use Of Food Parenting Practicesmentioning
confidence: 99%